ALTERNATIF PAKAN IKAN MENGGUNAKAN ULAT BSF SEBAGAI LANGKAH MENERAPKAN MANAJEMEN PAKAN - Dwi Septi Haryani; Evita Sandra; Muhammad Mu’azamsyah; Afri Lien Syahvitri; Doni Andika; Fikri Andani; Maharani Maharani; Nadia Rosita Pandiangan; Geaby Desrianti; Megi Rizky Eka Putri (Bajang Institute, 2023)
The purpose of this activity is to provide knowledge about feed management and reduce animal feed capital by cultivating BSF caterpillars. Community service is carried out in Toapaya Village, North Bintan District, Bintan Regency by involving community groups and fish farmers. The community involved in community service involved in this community service is 35 people, then the Community Service Team consists of 1 lecturer and 21 students. Counseling and socialization were carried out to community groups in Toapaya Village, socialization was carried out at the Toapaya Village Hall. Counseling to the community is carried out to socialize the activities carried out. BSF caterpillar cultivation that is socialized and applied in the community is able to become an alternative to fish feed using BSF caterpillars as a step to implement effective and efficient feed management. From the results of community service, it was obtained to increase the ability of the community to manage feed 100%, from not knowing to knowing and skilling. The socialization process has increased the community's expertise in managing feed which then becomes an alternative to fish feed as a step to implement effective and efficient feed management. From the results of this community service, we also suggest that the cultivation of BSF caterpillars be carried out in order to be able to reduce feed capital